Computation, Logic, Games, and Quantum Foundations. The Many Facets of Samson Abramsky Essays Dedicated to Samson Abramsky on the Occasion of His 60th Birthday - Coecke, Bob.; Ong, Luke.; Panangaden, Prakash; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This Festschrift volume, published in honor of Samson Abramsky, contains contributions written by some of his colleagues, former students, and friends. In celebration of the 60th birthday of Samson Abramsky, a conference was held in Oxford, UK, during May 28-30, 2010. The papers in this volume represent his manifold contributions to semantics, logic, games, and quantum mechanics.
Use of a Canonical Hidden-Variable Space in Quantum Mechanics -- Imperfect Information in Logic and Concurrent Games -- Compositional Quantum Logic -- The Algebra of Directed Acyclic Graphs -- Diagrammatic Reasoning for Delay-Insensitive Asynchronous Circuits -- Payoffs, Intensionality and Abstraction in Games -- On the Theory of Composition in Physics -- On the Functor 2 -- Quantum Speedup and Categorical Distributivity -- Unifying Semantics for Concurrent Programming -- Unfixing the Fixpoint: The Theories of the (Sn(BY -Calculus -- Continuous Domain Theory in Logical Form -- Presheaf Models of Quantum Computation: An Outline -- Nothing Can Be Fixed -- Dialogue Categories and Frobenius Monoids -- Anatomy of a Domain of Continuous Random Variables II -- Towards Nominal Abramsky -- Techniques for Formal Modelling and Analysis of Quantum Systems -- Quantum Field Theory for Legspinners -- Bicompletions of Distance Matrices -- Partial Recursive Functions and Finality -- Breaking the Atom with Samson -- Reasoning about Strategies -- Domain Theory in Topical Form -- Kolmogorov Complexity of Categories.s
Keywords: Computer science; Software engineering; Computer software; Logic design; Computer Science; Logics and Meanings of Programs; Computation by Abstract Devices; Mathematical Logic and Formal Languages; Algorithm Analysis and Problem Complexity; Software Engineering; Programming Languages, Compilers, Interpreters